EXPERIENCE WITH AND PERCEPTION OF CLIL BY STUDENT TEACHERS - Lukáčová, Zuzana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Content and Language Integrated Learning (CLIL) plays a key role in addressing the issue of meaningful and authentic learning. Central to this approach is the concept of a foreign language in a meaningful context while taking into consideration dual aims, i.e. a linguistic and a content aim. The purpose of this paper is to review recent research into the problematics of CLIL and its implementation at primary, lower-secondary and upper-secondary schools as well as to explore the experience with and perception of student teachers towards the CLIL approach. The data were obtained from a semi-structured questionnaire distributed among student teachers of English language and literature (in combination). Based on the data obtained, approximately half of the respondents have had an experience with the CLIL approach in the past. Moreover, the majority of the respondents perceive such an experience as positive.  Student teachers' previous experience with CLIL can play an important role in addressing the issue of implementing this approach into teaching by teachers – beginners. Thus, it is believed that the paper will contribute to our understanding of the approach, its implementation at primary, lower-secondary, upper-secondary schools and the perception of the approach by the student teachers of English (in combination) in Slovakia.